Introduction to theoretical and computational fluid dynamics - Pozrikidis, C. (Oxford University Press, 1997)
This book offers a comprehensive and rigorous introduction to the fundamental principles and equations that govern the kinematics and dynamics of the laminar flow of incompressible Newtonian fluids. It simultaneously illustrates the application of numerical methods to solving a broad range of problems drawn from diverse areas, and discusses the development of pertinent computational algorithms. Topics considered include the description and analysis of flow kinematics; the computation of exact solutions of hydrostatics and hydrodynamics by solving ordinary differential equations; the study and computation of potential flow; the theory and numerical study of flow at low Reynolds numbers, linear hydrodynamic stability, and vortex motion; boundary-integral methods for potential and Stokes flow; and finite-difference methods for the Navier-Stokes equation. An appendix contains a primer of numerical methods that allows for ready reference